Rethinking the hedonic treadmill within the context of Broaden and Build theory: developing resources through positive employees - Mills, Maura Josephine (Kansas State University, 2010)
Entrenched within the sphere of positive psychology, the present series of studies takes a progressive approach to understanding and furthering the practical application of constructs subsumed within the subfield of positive organizational behavior (POB). The progression begins with Study 1, which analyzes the factorial structure and psychometric footholds of the primary measurement instrument for Psychological Capital (PsyCap), one of the newer positive psychological constructs. This study suggested that both the measurement of this construct in addition to its factor structure may need to be reevaluated in order to best conceptualize the multifactorial nature of this variable. In turn, Study 2 involves resilience, one of the four aspects of PsyCap, and suggests that it may play an important role in molding employees’ work experiences. Specifically, Study 2 explores the relations between workload and eudaimonic and hedonic well-being over a two-week period, finding that workload is negatively related to eudaimonic well-being, but, interestingly, positively related to hedonic well-being. However, hypotheses suggesting that resilience and role salience may independently moderate workload’s relations with eudaimonic and hedonic well-being were not supported. Finally, recognizing the potential value of these positive psychological constructs (resilience and well-being in particular) for employers and employees alike, Study 3 aimed to develop interventions capable of increasing individuals’ positive personal resources, whereby they may enhance their ability to endure work challenges and even thrive in the face of such challenges. Findings indicated that the intervention targeting resilience did not result in significant differences between a control group and the intervention group. The intervention targeting well-being resulted in no differences in hedonic well-being, but did evidence differences on the personal growth aspect of eudaimonic well-being. Overall, these three studies taken together speak to the applicability of positive organizational behavior constructs in the workplace, and how such constructs might be enhanced in employees.
Keywords: Positive psychology; Positive organizational behavior; Resilience; Well-being; Intervention; Hierarchical linear modeling; Psychology, Industrial (0624)